2022
DOI: 10.1097/j.pain.0000000000002711
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pain, fatigue, and function between post–COVID-19 condition, fibromyalgia, and chronic fatigue syndrome: a survey study

Abstract: Supplemental Digital Content is Available in the Text.Individuals with post–Coronavirus-19 condition report elevated pain, fatigue, psychological impact, and functional limitation similar, but less severe, than those with fibromyalgia and chronic fatigue syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 147 publications
(263 reference statements)
3
19
0
Order By: Relevance
“…However, Schulze and colleagues demonstrated that fatigue was not associated with symptoms of anxiety or depression in males and females with post-COVID-19 symptoms (Schulze et al 2022 ). Moreover, Peterson et al demonstrated that conditioned pain modulation was impaired in people who had symptomatic acute COVID-19 (Peterson et al 2022 ) and Haider et al found that pain levels in people with post-COVID-19 symptoms are comparable to people with fibromyalgia and chronic fatigue syndrome (Haider et al 2022 ), which is line with the results of the current study. Additionally, it has been suggested that self-reporting post-COVID-19 symptoms may be influenced by one’s perception of the COVID-19 pandemic and apprehension about developing post-COVID-19 symptoms (Engelmann et al 2022 ; Matta et al 2022 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, Schulze and colleagues demonstrated that fatigue was not associated with symptoms of anxiety or depression in males and females with post-COVID-19 symptoms (Schulze et al 2022 ). Moreover, Peterson et al demonstrated that conditioned pain modulation was impaired in people who had symptomatic acute COVID-19 (Peterson et al 2022 ) and Haider et al found that pain levels in people with post-COVID-19 symptoms are comparable to people with fibromyalgia and chronic fatigue syndrome (Haider et al 2022 ), which is line with the results of the current study. Additionally, it has been suggested that self-reporting post-COVID-19 symptoms may be influenced by one’s perception of the COVID-19 pandemic and apprehension about developing post-COVID-19 symptoms (Engelmann et al 2022 ; Matta et al 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…The main findings were that subjects with post-COVID-19 symptoms reported higher levels of fatigue and perceived fatigability than subjects without post-COVID-19 symptoms, but there were no differences in objective fatigability between the groups. Furthermore, people with post-COVID-19 symptoms reported worse fatigue-related factors, such as increased pain and decreased quality of life, which has been demonstrated in other studies in people with post-COVID-19 symptoms (Haider et al 2022 ; Peterson et al 2022 ) and is common in other neurological disorders (e.g., multiple sclerosis and chronic fatigue syndrome) (Harrison et al 2015 ; Heitmann et al 2016 ; Workman et al 2020a , 2020c ). These findings support our hypothesis regarding perceived and objectively determined fatigability.…”
Section: Discussionsupporting
confidence: 63%
“…If the results of this RCT are strong enough in terms of efficacy and cost-utility, FIBRO-Out and/or FIBRO-On could be considered for their inclusion in the public healthcare Spanish system to treat individuals suffering from FM. Additionally, this RCT may also pave the way for further RCTs testing the efficacy of these interventions in other chronic diseases cursing with central sensitization (e.g., irritable bowel syndrome, chronic headache, temporomandibular disorder, pelvic pain syndromes), along with other emerging conditions such as persistent post-COVID syndrome which may display overlapped symptoms with FM ( Haider et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same type of symptomatology resembles features of another nociplastic pain condition such as fibromyalgia syndrome. Haider et al have recently confirmed that patients with long-COVID share a similar phenotype to those with fibromyalgia or chronic fatigue syndrome, but with less severe pain and fatigue overall (Haider et al, 2023).…”
Section: Nociplastic Painmentioning
confidence: 93%